Quality and Vision in the Romanian Tourism Agencies - Anca Atanase; Ion Schileru (Amfiteatru Economic Journal, 2014)
The investments in tourism concern mainly the qualitative structure of touristic service, with mainly material character, objectively assessable, and less the qualitative conduct part. However, most important for providing high quality services in tourism is the information, good practice in the field, human resource. Therefore, one has to invest in the selection, recruitment, training and better motivation of the staff, requiring the knowledge, experience, skills, responsibility, its entire involvement, the results being useful in the evolution of the organisation and the field. It is noticed in the field of Romanian tourism the need to satisfy the requirements of the client as well as the existence of some patterns, requirements or quality standards, being necessary to focus on the increase in the ability to achieve the quality requirements, with a view to improve the quality of tourism services. The reference objectives of the work's authors are the identification of optimum criteria of appreciation for the touristic services / products, the supply of some elements of good practice in the field, the conception of quality standards applicable in tourism organisations. The authors of the work consider relevant for the academic environment to bring in foreground some fundamental elements in tourism quality, the need to perform more advanced tests related to the consumer's degree of satisfaction towards touristic services and their quality level, focusing on solutions such as: designing quality touristic products, the qualification of the staff in the field, good practice specific to organisations that implemented the quality management system. In this respect, the authors of the work researched the normative frame, the speciality literature and press, assessed the perceptions related to service quality in tourism, analysing them on Romania's level, pointing topics and elements meant to assure the development of this field in the future. Authors also used a methodology specific to the quality management systems in the field of services.
Keywords: L83; L15; M10; 330; quality in tourism; quality management in tourism; good practice in tourism